2010
DOI: 10.1007/s11431-010-4067-4
|View full text |Cite
|
Sign up to set email alerts
|

Constructal entransy dissipation rate and flow-resistance minimizations for cooling channels

Abstract: Based on constructal theory, a construct of a volume that generates heat at every point and is cooled by the coolant in the constant or tapered channel is optimized by minimizing entransy dissipation rate and flow resistance. The optimal constructs of the rectangular elements with dimensionless mean thermal resistance minimization as well as the first-, second-and third-order assemblies with dimensionless global flow resistance minimizations are obtained respectively. The results show that both the mean temper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
13
0
2

Year Published

2010
2010
2012
2012

Publication Types

Select...
9

Relationship

6
3

Authors

Journals

citations
Cited by 40 publications
(15 citation statements)
references
References 52 publications
0
13
0
2
Order By: Relevance
“…Finally, the element to the third order assembly with tapered channels are re-optimized. The optimization results are shown as follows [162,163]:…”
Section: Numerical Optimizations Of the Cavity Heat Dissipationsmentioning
confidence: 99%
“…Finally, the element to the third order assembly with tapered channels are re-optimized. The optimization results are shown as follows [162,163]:…”
Section: Numerical Optimizations Of the Cavity Heat Dissipationsmentioning
confidence: 99%
“…Optimization results showed that constructs based on EDR minimization could decrease the mean temperature difference more effectively than those based on MTD (maximum temperature difference) minimization. Soon after, Wei et al [80][81][82][83][84], Xie et al [85][86][87] and Xiao et al [88,89] conducted constructal optimizations for a series of heat transfer problems. Based on ref.…”
Section: Introductionmentioning
confidence: 99%
“…With the concept of entransy dissipation or thermal resistance based on entransy dissipation, researchers have conducted many optimization studies of heat conduction, heat convection and mass convection [17][18][19][20][21][22][23]. Chen and co-authors [21][22][23] combined the extremum entransy dissipation principle with the constructal theory and optimized many heat transfer systems based on entransy dissipation rate minimization. In researches of heat exchangers and HENs, Song et al [24] demonstrated the uniformity principle of temperature difference field for one-dimensional heat exchanger based on the extremum entransy dissipation principle.…”
mentioning
confidence: 99%